RETORNOS DE CAPITU - Weinhardt, Marilene (Revista Letras, 2003)
Identificação dos textos ficcionais contemporâneos que dialogam com Dom Casmurro ou com a personagem empírica do autor e caracterização dos processos intertextuais empregados pelos ficcionistas. Abstract An identifying of contemporary fictional texts which dialogue with Dom Casmurro or with the empirical character of the author and a characterization of intertextual process applied by writers.